Representing others' actions: just like one's own? - Sebanz, Natalie; Knoblich, Günther; Prinz, Wolfgang (Cognition, 2003)
Previous research has shown that observing others' actions can affect individual performance of the same actions. In the present study, we developed a new paradigm to investigate whether and how complementary actions at the disposal of another agent are represented and influence one's own actions. A spatial compatibility task was distributed among two people so that each participant took care of one of two responses. The identical task was performed alone and alongside another participant. There was a spatial compatibility effect in the group setting only. It was similar to the effect obtained when one person took care of both responses. This result suggests that one's own actions and others' actions are represented in a functionally equivalent way.